Elastisitas Pendapatan dan Pola Konsumsi Rumah Tangga: Studi pada Masyarakat Perkotaan Menengah - Erickson Sinaga; Mario Purba; Wendi Rehan Situmorang; Gracelino Prasetyo Nainggolan; Jogi Situmorang; Ruben Boot (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to explore the relationship between income and household consumption patterns among urban middle-class families. Using secondary data from Indonesia’s Central Bureau of Statistics (BPS) for 2022–2023, the research analyzes income elasticity across four categories: rice, clothing, dining out, and vacations. The results classify rice and clothing as normal goods, while dining out and vacations are identified as luxury goods. These findings align with Engel’s Law, indicating a shift in consumption from basic needs to lifestyle and leisure as income increases. The study provides useful insights for businesses and policymakers in designing strategies tailored to urban middle-class consumer behavior.